2009
DOI: 10.1097/yic.0b013e32832c25d7
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week, naturalistic switch study of the efficacy and tolerability of aripiprazole in stable outpatients with schizophrenia or schizoaffective disorder

Abstract: The objectives of this 12-week multicenter open-label switching study were to evaluate the overall clinical efficacy, safety, and tolerability of aripiprazole in stable patients with schizophrenia or schizoaffective disorder, and to assess, in a naturalistic setting, whether such patients experience symptom worsening when switched from D2 receptor antagonists to aripiprazole (a D2 receptor partial agonist). Patients with schizophrenia or schizoaffective disorder in a symptomatically stable state were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Therefore, olanzapine at 3 mg/kg is a side effect dose. Accumulating evidence shows that switching to aripiprazole may provide favorable outcomes by potentially improving psychosis and by decreasing metabolic problems such as weight gain . However, aripiprazole may transiently worsen psychosis in some cases after an abrupt discontinuation of a prior atypical antipsychotic drug .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, olanzapine at 3 mg/kg is a side effect dose. Accumulating evidence shows that switching to aripiprazole may provide favorable outcomes by potentially improving psychosis and by decreasing metabolic problems such as weight gain . However, aripiprazole may transiently worsen psychosis in some cases after an abrupt discontinuation of a prior atypical antipsychotic drug .…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated an improvement in symptomatic remission rate after the 12-week treatment of paliperidone ER. Another study showed that the remission rate was increased from 43.9% at baseline to 51.7% at 12 weeks after aripiprazole treatment [29]. The original RSWG criteria requires 6 month duration, we have not used the criteria for remission as originally defined.…”
Section: Discussionmentioning
confidence: 99%
“…These switching failures were speculated to be attributable to its unique receptor profile of DPA ( Takeuchi et al., 2009 ). Indeed several ARI trials suggested that a switching method of concomitant ARI initiation and tapering off of the current medication could cause a relapse of psychosis ( Lin et al., 2009 ; Pae et al., 2009 ), although this result was not always confirmed in other trials ( Casey et al., 2003 ; Kim et al., 2009 ). In addition, Pae and colleagues noticed a possible association between psychotic relapse following switching to ARI and DSP ( Pae, 2009 ; Pae et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%